Australian women's self‐perceived barriers to participation in cervical cancer screening: A systematic review. (7th August 2019) - Nagendiram, Archana; Bougher, Hannah; Banks, Jennifer; Hall, Leanne; Heal, Clare
Abstract: Background: Australia has recently introduced a new screening program for cervical cancer. There has also been a decline in participation rates for cervical screening. Aim: To complete a systematic literature review of the factors that prevent Australian women from participating in cervical screening. Methods: Authors searched CINAHL, Medline, SCOPUS and the Cochrane Library to obtain articles discussing Australian women's self‐identified barriers to cervical screening. Quantitative studies published in peer‐reviewed journals after 1991 were considered. PROSPERO Registration Number: CRD42018105028. Results: The final search produced 1749 studies, with 13 quantitative papers included in the narrative synthesis after screening by two independent reviewers. No articles were excluded due to bias. Discussion: Self‐identified barriers to screening were categorised into personal, practitioner, test‐related and logistical factors. The most commonly stated barriers included lack of time, embarrassment, fear of results, irrelevance and male health professionals. The use of HPV triage in cervical screening was not a barrier to screening, however, some women regarded self‐collected HPV testing as a barrier. Barriers to self‐collection included desire for the general practitioner to complete the test, fear of doing the test incorrectly, wishing to include it in a general check‐up and concerns about the test itself. Conclusion: A variety of personal, practitioner, test‐related and logistical barriers negatively impact the screening participation of Australian women. Further research into barriers in the Australian population, and women's attitudes towards HPV testing and self‐collection is required to create effective health interventions to improve participation in cervical screening.